Livets mening på Lakolk strand: Horisontal fordomsfrihed i Peter Seebergs roman Ved havet - Barnwell, Jeppe (K&K - Kultur og Klasse, 2020)
Ved havet (“At the Seaside”, 1978) by the Danish author Peter Seeberg (1925-99) is a complex novel that portrays approximately 40 people on a day at the beach of Rømø Island. It has often either been construed as a biblically inspired narrative or expounded in the light of a Nietzschean amor fati (love of faith). As an alternative, I suggest an interpretation grounded on a conception of the beach as a particular and privileged space, eternal yet open and liable to change, which allows a plurality of voices and views to coexist peacefully in what I call a horizontal open-mindedness. I argue that the novel grapples with a classic modernistic idea about existence—and in particular a symbolistic idea about transcendence—but that it does it in a new, more sensorial and inclusive way. By comparing the novel to, among other things, an unpublished essay on “the meaning of life on Lakolk Beach,” I propose a reading that points towards a new postmodern “realism” in the writings of Seeberg and perhaps in Danish literature on the whole.